ACCUMULATION OF GAS HYDRATES AND COMPACTION OF ACCUMULATED SEDIMENTS: THE PROBLEM OF INTERRELATION BETWEEN THE PROCESSES - Suetnova E.I. (My University, 2007)
Heating of sediments and their compaction accompanied by filtration of pore fluids to the surface are the basic processes of heat-and-mass transfer, which occur during formation of sedimentary sequences on the geological time scale. However, filtration of pore fluids containing dissolved gas to the surface, many cases of which are described in the scientific literature, leads to the formation of layers saturated with gas hydrates at different depths in the sedimentary column, because pressures and temperatures favorable for the formation and stability of gas hydrates are widespread in the structures of the ocean floor. If the amount of gas is sufficient, gas hydrates are formed.